Analysis of the Symptomatology, Disease Course, and Treatment of Postorgasmic Illness Syndrome in a Large Sample. Issue 11 (30th September 2020) - Natale, Caleb; Gabrielson, Andrew; Tue Nguyen, Hoang Minh; Dick, Brian; Hellstrom, Wayne J.G.
Abstract: Background: Postorgasmic illness syndrome (POIS) is a rare syndrome of unknown etiology where patients experience distressing physical and psychological after ejaculatory sequelae. Aim: To better characterize the epidemiology, symptomatology, disease course, and treatment of POIS, with specific interest placed on examining relationships between disease presentation and measures of disease burden. Methods: A 30-item questionnaire was distributed to an online community of patients with POIS from June 2019 to January 2020. We assessed diagnostic criteria and clusters of symptomatology described in prior studies. Outcome measures include self-reported measures of symptom severity, disease burden, and behavioral changes. Statistical correlations were assessed with Pearson's chi-squared (χ 2 ) and ordinal regression analyses. Outcomes: The main outcome measures of this study are self-reported measures of symptom severity, disease burden, and behavioral changes. Results: The sample consisted of 302 men (mean age: 32.6 ± 11.4 years, mean age of onset: 19.1 ± 7.8 years) with 89% satisfying ≥3 diagnostic criteria. Common symptoms were difficulty concentrating (254, 84%), extreme fatigue (250, 83%), irritability (225, 74%), and muscle weakness (212, 70%). Common symptom clusters were general (219, 72%), muscle (137, 45%), and head (93, 31%). Common behavioral modifications were avoiding masturbation (215, 71%), schedule changes (213, 71%), and abstinence (186, 62%). Head and throat symptom clusters demonstrated worse disease burden outcomes. Professional medical advice was sought by 51% of participants. Attempted treatments included pharmacotherapy, vitamins, supplements, and herbs with variable efficacy. Clinical Implications: This study further characterizes POIS, including how patients respond to the condition, how it is treated in the community, and presentations that may be associated with more severe disease. Strengths & Limitations: This is the largest study to date that concerns patients suffering from POIS and includes a diverse, global population. Limitations include that the survey was only administered in English and within 1 online community, that results were self-reported, and that the response rate was low (32%). Conclusions: Characterizing symptom cluster, but not number of diagnostic criteria, may offer prognostic value, and investigation to elucidate pathophysiology and potential treatments for POIS is necessary.